2011
DOI: 10.17221/40/2010-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Stable Agrobacterium-mediated transformation of Norway spruce embryogenic tissues using somatic embryo explants

Abstract: in conifers and other plants with long reproductive cycles, transformed embryogenic tissues can serve as a convenient source of plant material for the testing of insecticidal or fungicidal transgene efficiency. in this report, transgenic embryogenic tissue was obtained after the transformation of somatic embryos of norway spruce (Picea abies (l.) Karst.) by Agrobacterium tumefaciens with the gus-intron chimeric gene. the stable integration of transgenes was confirmed by Pcr and southern hybridization. the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although kanamycin is the most widely used antibiotic for plant transformation, few reports about the successful use of kanamycin in maritime pine have been made [ 10 , 13 ]. In conifers, kanamycin selection seems to be a good choice for zygotic embryos of Picea glauca [ 14 ], Larix kaempferi X L. decidua [ 15 ], Pinus taeda [ 16 ], and Pinus strobus [ 17 ] and somatic embryos of Picea abies [ 18 ], Pinus strobus [ 19 , 20 ], and Pinus radiata [ 21 ]. However, it was problematic in cotyledons of Pinus radiata [ 22 ], P. pinea [ 23 ], and P nigra [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although kanamycin is the most widely used antibiotic for plant transformation, few reports about the successful use of kanamycin in maritime pine have been made [ 10 , 13 ]. In conifers, kanamycin selection seems to be a good choice for zygotic embryos of Picea glauca [ 14 ], Larix kaempferi X L. decidua [ 15 ], Pinus taeda [ 16 ], and Pinus strobus [ 17 ] and somatic embryos of Picea abies [ 18 ], Pinus strobus [ 19 , 20 ], and Pinus radiata [ 21 ]. However, it was problematic in cotyledons of Pinus radiata [ 22 ], P. pinea [ 23 ], and P nigra [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include plant material, Agrobacterium strain and co-cultivation time and so on. Rapid growth of the source material is important for transformation of Norway spruce (Pavingerová et al, 2011), Pinus pinaster (Tereso et al, 2006), and chir pine (Parasharami et al, 2006), and may contribute to the success observed in this study.…”
Section: Ems Confirmed As Transformants By Gus Staining Andmentioning
confidence: 78%
“…Currently Agrobacterium-mediated gene transfer is the useful method for most of plant biotechnology laboratories because of the high percentage of single-copy and single-locus insertion events compared to other plant transformation techniques (Aronen et al, 2007;Klimazewska et al, 1997;Newton, 2001;Parasharami et al, 2006;Pavingerová et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Literature concerning the P. abies somatic embryos genetic transformation is very scarce due to difficulty in obtaining transgenic callus. In a study conducted by Pavingerová et al [135], only one of the nine tested lines of cotyledonary somatic embryos were able to produce transgenic callus.…”
Section: Se-the Future Of Forestry? 61 Applied Biotechnology and Sementioning
confidence: 96%
“…Currently, several reports concerning the genetic transformation of P. abies embryogenic cultures are available [133][134][135][136]. Most studies were carried out on embryogenic tissues using Agrobacterium tumefaciens-mediated transformation.…”
Section: Se-the Future Of Forestry? 61 Applied Biotechnology and Sementioning
confidence: 99%